2011
DOI: 10.1111/j.1574-695x.2011.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive proteins ofCampylobacter concisus, an emergent intestinal pathogen

Abstract: Campylobacter concisus is an emerging pathogen of the human gastrointestinal tract. Recently, a significantly higher prevalence of C. concisus DNA and higher levels of antibodies specific to C. concisus was detected in children with Crohn's disease when compared with controls. The aim of this study was to identify C. concisus immunoreactive antigens. Proteins from C. concisus were separated using two-dimensional gel electrophoresis, and sera from 10 C. concisus-positive children with Crohn's disease were emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Further studies conducted by us and others, have supported this finding in patients with CD71 107 108 and UC 29 70 72 109. Moreover, recent advances suggest that C. concisus is an immunogenic micro-organism as C. concisus flagellin B, ATP synthase F1 α subunit and outer membrane protein 18 have been shown to be consistently recognised by all patients with CD110 while Campylobacteraceae DNA has been found in the lymph nodes of patients with CD 111…”
Section: Discussionmentioning
confidence: 62%
“…Further studies conducted by us and others, have supported this finding in patients with CD71 107 108 and UC 29 70 72 109. Moreover, recent advances suggest that C. concisus is an immunogenic micro-organism as C. concisus flagellin B, ATP synthase F1 α subunit and outer membrane protein 18 have been shown to be consistently recognised by all patients with CD110 while Campylobacteraceae DNA has been found in the lymph nodes of patients with CD 111…”
Section: Discussionmentioning
confidence: 62%
“…In line with this, a study by Kovach and colleagues identified 37 immunoreactive proteins of C. concisus, detected using sera collected from 10 C. concisus-positive children with CD (97). Of these proteins, flagellin B, the ATP synthase F1 ␣ subunit, and outer membrane protein 18 were consistently recognized by all CD patients (97).…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 54%
“…Infection with C. concisus can predispose individuals to the development of microscopic colitis and irritable bowel syndrome (6,7). Furthermore, this bacterium has been associated with the development of more severe chronic conditions, such as inflammatory bowel diseases (IBD) (8)(9)(10)(11)(12)(13)) and Barrett's esophagus (14,15).…”
mentioning
confidence: 99%